Teknik Steganography untuk Menyisipkan Pesan pada Sebuah Citra Menggunakan Metode Least Significant Bit (LSB) - Khuzaifi, Ahmad; Fauziah, Fauziah; Fitri, Iskandar (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Copyright is a direct right granted to the creator of a work in any form that is real and recognized in accordance with the provisions of the legislation in force in the area. Copyright infringement is very detrimental to the creators of works who have tried hard in creating a work. The steganography technique can be a solution to insert hidden messages into digital data. In writing this scientific research journal, an application was made to give a hidden message sign to an image. The goal is to protect copyrighted works from being easily recognized by irresponsible parties. Making this simple application using MATLAB R2021a software. By using the Least Significant Bit [LSB] method, what happens is that the data bits will be inserted into the digital image bit by changing the last bit. The result is that the image inserted with the message does not experience significant changes, but when the image undergoes an extraction process, the inserted message will appear. The results of the Least Significant Bit [LSB] method in this study are successful in inserting a .txt file into the hidden original image so that it does not change the visualization of the image but only changes the image size from 56.9KB to 732KB